Analysis and Design of Mangrove Ecotourism Management System (SIMANGROVE) of Dodola Island, Morotai Island Regency, Indonesia - Heru Prasadja; Yerik Afrianto Singgalen (Universitas Bina Darma, 2022)
Tourism destination managers need information systems necessary for tourism destination managers to optimise the ecological, economic, and socio-cultural monitoring functions. This study aims to develop a management information system known as SIMANGROVE based on the context of managing mangrove areas in Dodola Island of Morotai Island Regency, Indonesia. The system design is carried out using the Software Development Life Cycle (SDLC) framework through the Waterfall approach. The analysis of the concept of mangrove ecotourism is adjusted to the availability of resources classified into accessibility, accommodation, attractions, and amenities on Dodola Island. The research of analysis and design of SIMANGROVE show that the ease of use of the application (usability), quality of information (information) and user security (security) are essential elements that benefit managers and visitors when accessing data as well as making reservations and transactions in the SIMANGROVE system.